1966
DOI: 10.1177/001440296603200705
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Speech Therapy for Second Grade Children with Misarticulations—Predictive Factors

Abstract: The purpose of this study was to evaluate speech therapy for functional misarticulations and to determine the measures which predict improvement in speech, language, and listening. The following factors appeared predictive: (a) occupational status of the fathers and word recognition; (b) mental age and improvement in word recognition, auditory discrimination, and articulation; (c) stimulability of sounds and improvement in articulation; (d) auditory skills and improvement in connected speech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Past research indicates that stimulability may be used to predict the potential for improvement in speech sound production with and without treatment (Carter & Buck, 1958;Diedrich, 1983;Farquhar, 1961;Irwin, West, & Trombetta, 1966;Snow & Milisen, 1954;Somers et al, 1967). Kindergarten, first and second grade children with poor stimulability skills benefit greatly from treatment (Carter & Buck, 1958;Somers et al, 1967).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Past research indicates that stimulability may be used to predict the potential for improvement in speech sound production with and without treatment (Carter & Buck, 1958;Diedrich, 1983;Farquhar, 1961;Irwin, West, & Trombetta, 1966;Snow & Milisen, 1954;Somers et al, 1967). Kindergarten, first and second grade children with poor stimulability skills benefit greatly from treatment (Carter & Buck, 1958;Somers et al, 1967).…”
mentioning
confidence: 99%
“…Kindergarten, first and second grade children with poor stimulability skills benefit greatly from treatment (Carter & Buck, 1958;Somers et al, 1967). Of children in the first and second grades who do not receive treatment, those with high stimulability scores demonstrate significant improvement (Carter & Buck, 1958;Irwin et al, 1966;Snow & Milisen, 1954).…”
mentioning
confidence: 99%
“…Included are such measures as number of articulatory errors or when stimulated with the correct production of the sound, the ability to learn other sounds and performances on speech sound discrimination tests. Irwin, West & Trombetta (1966) found that the number of sounds misarticulated has predictive value. Farquhar (1961) discovered that the articulatory discrimination skills of nursery kids did not predict their articulation development.…”
mentioning
confidence: 99%